(untitled) (Journal of the Sociology and Theory of Religion, 2020)
The internationalization of universities is a tool that allows both teachers and students to have a broader view of the world. In this way, they acquire greater formative maturity, human networks are built and cooperate to continue researching. The Catholic universities of Colombia have International Relations Offices that seek to direct the academic and administrative units in the management of relations with other institutions at national and international level. Especially important are the agreements with other universities in which the parties will work together in activities that they consider of mutual interest to contribute to the development of cooperation between both institutions.